THE ROLE OF LABOR TRAINING AND PROTECTION IN INCREASING PERFORMANCE EFFECTIVENESS AT THE INDUSTRY AND EMPLOYMENT SERVICES OF BADUNG REGENCY - Titha Paramita Pika, Putu Ayu; Diarsa, Raymundus Arkananta OKa (LPPM Univ. Ibn Khaldun Bogor, 2022)
Currently, there is an increasing demand of the community for the implementation of good and clean government (Good Govermance and Clean Government). Badung Regency Regional Regulation Number 8 of 2014 concerning the Implementation of Manpower Services as follows: That in line with the spirit of autonomy and mandatory affairs that must be carried out by local governments, by taking into account Law Number 32 of 2004 concerning Regional Government, local governments are given the authority to determine policies for determination and backing in various fields, one of which is the field of manpower. As an effort to provide labor services that are the authority and task of the government, training, and productivity, placement, coaching, supervision and protection of workers, are strategic steps in overcoming labor problems. Therefore, it is necessary to have a training mechanism, and the productivity, placement, coaching, supervision and protection of workers so that services to the community are faster and more appropriate in accordance with the spirit of regional autonomy. The job training program organized by the Badung Regency Manpower Office is a program that aims to improve the competence of Human Resources. The Badung Regency Government is committed so that people who take part in this job training program can open their businesses independently or get jobs according to their expertise so that this can reduce unemployment in Badung Regency. The purpose of this study is to determine the implementation of job training and the factors that hinder the successful implementation of job training programs in Badung Regency. The method in this study uses a descriptive qualitative method. The theoretical concept used in this study is Edward III's theory, namely 1) communication, 2) resources, 3) disposition, and 4) bureaucratic structure. The results of this study show that the implementation of the job training program has not been said to be optimal, namely from communication criteria and resources. In its implementation, there are still obstacles that occur such as 1) lack of instructors, 2) references to job training centers that are still small, and 3) budget constraints in the implementation of job training.